Peran Partai Politik dan Kalkulasi Elit Terhadap Karakteristik Koalisi (Studi Kasus : Pilkada Serentak di Kabupaten Karangasem dan Tabanan 2015) - Winasih, Ni Wayan Indra; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2016)
ABSTRACT Political party’s actor and elite calculation are undivided element on politics process. Which is the political party as the main pilar in demokratic system, and utilities of power and governs, also the elit position playing the good roleand directing the legislation. Which is taken by this reseach named the role of political party and elite calculation toward coalition characteristic on study case of joint election at Bali 2015. People’s unknowing about process of candidating and forming of coalition which having a privat tendency. The metodh which used in the reseach is qualitative reseach with case comparative, with the case would been researching are election on Tabanan and Karangasem regency. As the foreword theories which use for the structure of reseach it using the coalition theory, elite theory, and rational choise theory and some reseach found which are the political intentions as the basic coalition forming in election. The candidate having a connection with using as the consideration of party’s action in high level with dominant acts such big political party that given a relative freedom under their lower structure, however, the little party giving the more freedom for the local level in the districts. Keyword : Coalition, political party, local election, elite